Reductions in hypothalamic Gfap expression, glial cells and α-tanycytes in lean and hypermetabolic Gnasxl-deficient mice. Issue 1 (December 2016) - Holmes, Andrew; Wong, Shi; Pulix, Michela; Johnson, Kirsty; Horton, Niamh; Thomas, Patricia; de Magalhães, João; Plagge, Antonius
Abstract Background Neuronal and glial differentiation in the murine hypothalamus is not complete at birth, but continues over the first two weeks postnatally. Nutritional status and Leptin deficiency can influence the maturation of neuronal projections and glial patterns, and hypothalamic gliosis occurs in mouse models of obesity.Gnasxl constitutes an alternative transcript of the genomically imprintedGnas locus and encodes a variant of the signalling protein Gαs, termed XLαs, which is expressed in defined areas of the hypothalamus.Gnasxl -deficient mice show postnatal growth retardation and undernutrition, while surviving adults remain lean and hypermetabolic with increased sympathetic nervous system (SNS) activity. Effects of this knock-out on the hypothalamic neural network have not yet been investigated. Results RNAseq analysis for gene expression changes in hypothalami ofGnasxl -deficient mice indicatedGlial fibrillary acid protein (Gfap ) expression to be significantly down-regulated in adult samples. Histological analysis confirmed a reduction in Gfap-positive glial cell numbers specifically in the hypothalamus. This reduction was observed in adult tissue samples, whereas no difference was found in hypothalami of postnatal stages, indicating an adaptation in adultGnasxl -deficient mice to their earlier growth phenotype and hypermetabolism. Especially noticeable was a loss of many Gfap-positive α-tanycytes and their processes, which form part of the ependymal layer that lines the medial and dorsal regions of the 3rd ventricle, while β-tanycytes along the median eminence (ME) and infundibular recesses appeared unaffected. This was accompanied by local reductions in Vimentin and Nestin expression. Hypothalamic RNA levels of glial solute transporters were unchanged, indicating a potential compensatory up-regulation in the remaining astrocytes and tanycytes. Conclusion Gnasxl deficiency does not directly affect glial development in the hypothalamus, since it is expressed in neurons, and Gfap-positive astrocytes and tanycytes appear normal during early postnatal stages. The loss of Gfap-expressing cells in adult hypothalami appears to be a consequence of the postnatal undernutrition, hypoglycaemia and continued hypermetabolism and leanness ofGnasxl -deficient mice, which contrasts with gliosis observed in obese mouse models. Since α-tanycytes also function as adult neural progenitor cells, these findings might indicate further developmental abnormalities in hypothalamic formations ofGnasxl -deficient mice, potentially including neuronal composition and projections.